The role of Motives in choosing the formalist referencias in architecture: دور المحفزات في اختيار المرجعيات الشكلية في العمارة - Heaven Mohamad Alsheekh Hamo, Safwat Ibrahim-Bacha, M. Atalla Chikh Mohamad (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2022)
The research seeks to identify the most important Motives that can help the designer to choose the appropriate formalist referencias for his design. And it tries to prove its importance and its impact on the formulation and formation of architecture and expressive images in it. And it occupies a Special position in the practice of architectural design, due to its connection to the stage of composition and the derivation of ideas within the design process. After examining and analyzing a variety of examples, And the research has suggested classifying them into five main Motives: (Motives belong to the designer – Motives belong to the project - Motives belong to the site - Motives belong to the society - other Motives). showing examples of each type of these Motives. In the end, the research concluded the multiplicity and diversity of Motives that help the designer choose his formalist referencias. And their role in bringing creative ideas. In addition to the importance of Motives that belong to the society (as vocabulary of architectural heritage), especially in Arab projects, where the percentage of its use reached 45% of the studied cases. The research also concluded that the designer can also take advantage of all Motives surrounding him, and depended on more than one referencia in his design. Through it, we can develop the design process, by formulating Curricula based on starting from these Motives as a strategy for creative architectural design. To choose the appropriate formalist referencia for the design problem faced by the designer, and to achieve the goals he seeks, In a manner consistent with the project data and requirements.